Decreased proliferative capacity of aged dermal fibroblasts in a three dimensional matrix is associated with reduced IGF1R expression and activation - Bentov, Itay (2014)
Skin aging results in increased susceptibility to injury and impaired wound healing. Proliferation of fibroblasts is reduced in aged dermis, which contributes to delays in wound closure. Age-associated differences are regulated, in part, by local or systemic factors such as the IGF-1/IGF1R system. The aim of this study was to determine if expression and activation of IGF1R in aged human dermal fibroblasts, when compared to young fibroblasts, is associated with altered proliferative capacity in a 3D collagen matrix that better simulates the dermal extracellular matrix in vivo. The proliferation of young and aged human dermal fibroblasts in 3D collagen and its association with baseline levels of IGF1R expression were measured. The effect of stimulation and inhibition of Erk phosphorylation on the proliferative capacity of fibroblasts in a 3D collagen matrix was defined. Our results show that proliferation and Erk phosphorylation is reduced in aged dermal fibroblasts relative to young fibroblasts. Activation of Erk phosphorylation in aged fibroblasts is associated with a significant increase in fibroblast proliferation in 3D collagen.